Nutritional evaluation of cultivated fodder crops grown under agro-climate of Tripura - DATT, CHANDER; SINGH, N P (The Indian Journal of Animal Sciences, 2011)
The study was conducted to assess forage yield and nutritional characteristics of various crops including graminaceous (maize, sorghum, pearl millet, oat, jobâ€™s tears, napier hybrid, para grass, congo signal, signal grass, guinea grass, thin napier and broom grass) and leguminous (cowpea, rice bean, berseem, cluster bean/guar, soybean, stylo and perennial ground nut) introduced at the ICAR Research Complex, Tripura Centre. The average fresh forage yields of different forage crops were satisfactory and in the range reported elsewhere in the country with the exception of berseem and cluster bean which yielded lesser quantity of herbage. There were significant differences among the crops (graminaceous or leguminous) in terms of proximate principles, cell wall constituents, in vitro DM and OM digestibility (IVDMD and IVOMD) and metabolisable energy (ME) values. Leguminous fodders possessed higher level of CP, EE, IVDMD/ IVOMD and ME compared to graminaceous fodders while a reverse trend was observed for CF and cell wall components except ADL. Overall, CP and EE were positively correlated with IVDMD, IVOMD and ME values, however, CF, NDF, ADF and cellulose showed negative relationship with these parameters. ME value had a strong positive correlation with IVDMD and IVOMD levels in the fodders. Considering their herbage yield under tilla land (upland) conditions, they hold good potential for increasing the forage production and thus bridge the gap between demand and supply of nutrients particularly for ruminants and to raise their productivity in the state.Â